1999
DOI: 10.1902/jop.1999.70.8.829
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Longitudinal Changes in Radiographic Alveolar Bone Height and Probing Depth Measurements: Data From Postmenopausal Women

Abstract: The changes in these patients were probably due to systemic changes in bone health rather than to periodontal disease. However, the weak correlations between changes in attachment level and bone height are similar to recent studies of periodontal disease. Our results support suggestions in the literature that the link between changes in attachment and alveolar bone height is complex, perhaps because changes in the 2 tissue types are separated by a considerable time delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…However, the clinical significance of HRT in periodontal health is not well established. HRT was associated with a reduction of alveolar bone loss [6,25,27,28], but a number of studies failed to find an inverse correlation between alveolar bone density and severity of periodontal disease [4851]. Furthermore, some authors failed to demonstrate any beneficial effect of HRT on alveolar bone density/height [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical significance of HRT in periodontal health is not well established. HRT was associated with a reduction of alveolar bone loss [6,25,27,28], but a number of studies failed to find an inverse correlation between alveolar bone density and severity of periodontal disease [4851]. Furthermore, some authors failed to demonstrate any beneficial effect of HRT on alveolar bone density/height [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The association between clinical (soft tissue) measurements and alveolar bone loss has been explored in untreated patients with chronic periodontitis (CP) 4‐6 and in the absence of CP 7 . In a study of postmenopausal females in the absence of periodontal disease, changes in ABH and changes in CAL were only weakly associated based on site‐level data over a 2‐year follow‐up period 7 . In untreated, general populations with CP, CALs and baseline crestal bone height were significantly correlated, but changes in these measures over a 1‐year period beyond a defined threshold did not demonstrate good agreement 6 .…”
mentioning
confidence: 99%
“…A small study of patients with untreated destructive periodontal disease monitored for 1 year suggested that significant AL preceded oral bone loss 4 . The association between oral bone loss and clinical periodontal measures, such as CAL, appears to be complex, and there is some suggestion that there may be a time lag between changes in oral radiographic measures and changes in clinical periodontal measures 7 . However, the temporal association between clinical and radiographic CP measurements during periodontal maintenance has not been explored.…”
mentioning
confidence: 99%
“…However, a parallel relationship between them may be limited to a small group of the elderly since a few elderly people had severe alveolar bone resorption. Age-related alveolar bone loss is shown,1723 but disruption of the lamina dura was independent of the alveolar bone resorption in the canine and first molar. Moreover, decline in the presence of a lamina dura may be caused by atrophy since the lamina dura seemed to be fully developed from the tooth bud to eruption, and disruption of the lamina dura began around 20 years of age.…”
Section: Discussionmentioning
confidence: 94%
“…In humans age-related alveolar bone loss has also been reported 1723. The rate of bone loss increases between the ages of 33 and 57–68 years17 and between 65 and 75 years,20 in the incisors,18 in subjects with chronic obstructive pulmonary disease,21 and with systemic changes,23 although age-related alterations in the periodontium may not inevitably be manifested with the loss of alveolar bone 24…”
Section: Introductionmentioning
confidence: 99%